The Influence of Competence and Professionalism on Consumer Satisfaction at The Indonesian Nail Industry Association (PIKI) - Betti Setiawati; Harries Madiistriyatno; Nurwulan Kusumadewi (Dinasti Publisher, 2026)
This study has the following objectives: To determine the effect of competence on consumer satisfaction, To determine the effect of professionalism on consumer satisfaction and To determine the effect of competence and professionalism simultaneously on consumer satisfaction. The population in this study was 171 nail beauty consumers, the author narrowed the population by calculating the sample size using the Slovin technique of 120 customers. Competence (X₁) has a positive and significant effect on consumer satisfaction (Y), Professionalism (X₂) has a positive and significant effect on consumer satisfaction (Y), Competence (X₁) and professionalism (X₂) simultaneously have a positive and significant effect on consumer satisfaction (Y). This is proven through the ANOVA test with an F count value of 29.773 which is greater than Ftable of 2.68, and a significance value of 0.000 < 0.05, so the third hypothesis is accepted. The significant contribution of competence and professionalism to customer satisfaction is indicated by the R-square value of 0.337, indicating that 33.7% of the variation in customer satisfaction is influenced by competence and professionalism, while the remaining 66.3% is influenced by other factors not examined in this study, such as product quality, price, organizational image, after-sales service, and other external factors.